Creating Immersive Arabic Environments: Bī'ah Lughawiyyah Implementation in Islamic Boarding Schools - Ulviana Amelia Putri; Muflihah Muflihah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2026)
This study aims to describe and analyze the implementation strategies of bī’ah lughawiyyah in maharah al-kalam learning at Al-Muttaqin, Al-Buruj, and Darul Falah Amtsilati Islamic boarding schools. The focus of the study includes language program planning, communication habits, language use regulations, and evaluation mechanisms designed to improve students’ speaking skills. The research subjects consist of educators, and students, while the object of the study is language activities that represent the implementation of bī’ah lughawiyyah in daily learning practices. This research employs a descriptive qualitative field approach. Data were collected through observation, in-depth interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The analysis framework refers to the perspective of Mahmūd Kāmil al-Nāqah. The findings indicate that the implementation of bī’ah lughawiyyah is systematic, structured, and sustainable. Al-Muttaqin emphasizes vocabulary mastery and discipline, Al-Buruj focuses on intensive communicative activities, and Amtsilati applies nadham-based practice. These strategies improve students’ fluency, confidence, participation, and consistency in using Arabic actively and effectively every day.